Insecticide resistance in Anopheles arabiensis populations from Dakar and its suburbs: role of target site and metabolic resistance mechanisms - A. Kane Dia; O. Kalsom Guèye; E. Amadou Niang; S. Mocote Diédhiou; M. Demba Sy; Abdoulaye Konaté; Badara Samb; Abdoulaye Diop; Lassana Konaté; Ousmane Faye (Malaria Journal, 2018)
Abstract Background Urban malaria is an increasing concern in most of the sub-Saharan Africa countries. In Dakar, the capital city of Senegal, the malaria epidemiology has been complicated by recurrent flooding since 2005. The main vector control measure for malaria prevention in Dakar is the community use of long-lasting insecticide-treated nets. However, the increase of insecticide resistance reported in this area needs to be better understood for suitable resistance management. This study reports the situation of insecticide resistance and underlying mechanisms in Anopheles arabiensis populations from Dakar and its suburbs. Results All the populations tested showed resistance to almost all insecticides except organophosphates families, which remain the only lethal molecules. Piperonil butoxide (PBO) and ethacrinic acid (EA) the two synergists used, have respectively and significantly restored the susceptibility to DDT and permethrin of Anopheles population. Molecular identification of specimens revealed the presence of An. arabiensis only. Kdr genotyping showed the presence of the L1014F mutation (kdr-West) as well as L1014S (kdr-East). This L1014S mutation was found at very high frequencies (89.53%) in almost all districts surveyed, and in association with the L1014F (10.24%). Conclusion Results showed the contribution of both target-site and metabolic mechanisms in conferring pyrethroid resistance to An. arabiensis from the flooded areas of Dakar suburbs. These data, although preliminary, stress the need for close monitoring of the urban An. arabiensis populations for a suitable insecticide resistance management system to preserve core insecticide-based vector control tools in this flooded area.